Meso‐Microporous Nanosheet‐Constructed 3DOM Perovskites for Remarkable Photocatalytic Hydrogen Production - Zhao, Heng; Liu, Jing; Li, Chao‐Fan; Zhang, Xu; Li, Yu; Hu, Zhi‐Yi; Li, Bei; Chen, Zhangxin; Hu, Jinguang; Su, Bao‐Lian (Advanced functional materials, 2022)
Three‐dimensionally ordered macroporous (3DOM) structures have been widely utilized to largely enhance a photocatalytic activity. However, the common nanoparticles‐constructed 3DOM photocatalysts possess numerous grain boundaries, unavoidably leading to a fast recombination of photogenerated electrons and holes. Herein, for the first time, a hierarchically two‐dimensional (2D) meso‐microporous perovskite nanosheet‐constructed 3DOM CaTiO3 to significantly reduce the grain boundaries is designed and fabricated. Using carbon quantum dots (CQDs) as a metal‐free co‐catalyst, the 3DOM CQDs‐CaTiO3 exhibits an outstanding photocatalytic activity for hydrogen generation of 0.13 mmol h−1 (20 mg photocatalyst) with remarkable apparent quantum efficiency (QAY) of 14.55% at 365 nm monochromatic light. This unprecedented performance is endowed by the synergy of a macro‐meso‐microporosity architecture, a large surface area, enhanced light harvesting, and improved charge carriers separation and transport. Density functional theory calculations and finite difference time‐domain simulations further reveal the mechanism behind the enhanced separation of photogenerated electrons and holes. The present work demonstrates a trial on rationally designing meso‐microporous nanosheet‐constructed 3DOM perovskites for solar driven hydrogen production. A perovskite meso‐microporous nanosheet‐constructed 3DOM CaTiO3 decorated with CQDs is designed for remarkable photocatalytic hydrogen production in a noble‐metal free system. The as‐synthesized composite exhibits extremely enhanced photocatalytic activity owing to the easy mass transfer by the synergistic effect of macro‐meso‐microporosity, large surface area, enhanced light harvesting, and improved separation of charge carriers.